WATER SUPPLY RELIABILITY OF WATER WITH JUMPERS - , В. Г. (Municipal economy of cities (Technical science), 2013)
The possibility of engineering calculation of the reliability of water supply in the two strands of the two bridges. Try for example the specific values of basic indicators of reliability.